2022
DOI: 10.1101/2022.08.31.506095
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

More than a ligand: PD-L1 promotes oncolytic virus infection via a metabolic shift that inhibits the type I interferon pathway

Abstract: Targeting the PD-1/PD-L1 axis has transformed the field of immune-oncology. While conventional wisdom initially postulated that PD-L1 serves as the inert ligand for PD-1, an emerging body of literature suggests that PD-L1 has cell-intrinsic functions in immune and cancer cells. In line with these studies, here we show that engagement of PD-L1 via cellular ligands or agonistic antibodies, including those used in the clinic, potently inhibits the type I interferon pathway in cancer cells. Hampered type I interfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…We hypothesize that the suppression of GM-CSF and IFN- α may be a downstream consequence of the systemic rise in PD-L1. A recent study by Hodgins et al demonstrated that intracellular PD-L1 activity can reduce type I interferon production through metabolic alterations that increase glycolysis and reduce oxidative phosphorylation [ 52 ]. PD-L1 drives upregulation of the glycolytic pathway and results in the accumulation of pyruvate, which is converted into lactate, and cytoplasmic lactate buildup negatively regulates the production of type I interferons [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesize that the suppression of GM-CSF and IFN- α may be a downstream consequence of the systemic rise in PD-L1. A recent study by Hodgins et al demonstrated that intracellular PD-L1 activity can reduce type I interferon production through metabolic alterations that increase glycolysis and reduce oxidative phosphorylation [ 52 ]. PD-L1 drives upregulation of the glycolytic pathway and results in the accumulation of pyruvate, which is converted into lactate, and cytoplasmic lactate buildup negatively regulates the production of type I interferons [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Hodgins et al demonstrated that intracellular PD-L1 activity can reduce type I interferon production through metabolic alterations that increase glycolysis and reduce oxidative phosphorylation [ 52 ]. PD-L1 drives upregulation of the glycolytic pathway and results in the accumulation of pyruvate, which is converted into lactate, and cytoplasmic lactate buildup negatively regulates the production of type I interferons [ 52 ]. One possible mechanism for this inhibition is the lactate-induced inhibition of cGAS-STING signaling, a major driver of both type I interferons and NF- k B [ 26 , 53 ].…”
Section: Discussionmentioning
confidence: 99%